THE EFFECT OF EARLY FIBROBRONCHOSCOPIC SANITATION WITH HUMAN COLLAGEN TYPE 1 ON EPITHELIZATION OF DAMAGED TRACHEAL AND BRONCHIAL MUCOSA IN PATIENTS WITH INHALATION INJURY - A. V. Makarov; A. V. Mironov; I. Y. Galankina; S. V. Smirnov; I. N. Ponomaryov; N. V. Borovkova (Неотложная медицинская помощь, 2018)
Background. Inhalation trauma remains one of the most common and complex condition to be treated. Fibrobronchoscopic sanitation plays a significant role in the complex therapy of patients with inhalation trauma, allowing purulent necrotic discharge, soot and combustion products to be removed from the lumen of the tracheobronchial tree. We proposed a method for local treatment of mucosal lesions in inhalation trauma based on early endoscopic sanitation of the tracheobronchial tree with solutions of antiseptics followed by application of human type 1 collagen solution.Aim of study. To assess the effect of early fibroblochoscopic sanitation with application of human-type collagen 1 on the timing of epithelialization of the damaged tracheal and bronchial mucosa in patients with inhalation trauma.Material and methods. The study included 59 patients with inhalation trauma of 2–3 degree. All patients from the first day after the trauma underwent bronchoscopic sanitation in accordance with the standards of medical care. Immediately after the removal of soot, the solution of human-type collagen 1 was applied in patients of the main group, obtained from ligaments and tendons by the acid extraction method. The dynamics of the reparative process was evaluated on the basis of the endoscopic study and according to a series of morphological studies of the biopsy material obtained in the course of fibrobronchoscopy.Results. Complete epithelization of erosions of the mucous membrane of the trachea and bronchi in patients with inhalation trauma of 2 degree occurred significantly earlier (3 (2; 6) days) than without its application (7 (4; 9) day) (n1 =15; n2 =21; U=49.5; p=0.0004). In patients with inhalation trauma of 3 degree, epithelialization time was reduced from 17 (12; 22) days in the comparison group to 7 (6; 9) days in the main group (n1 =14; n2 =9; U=1; p=0.001). According to the morphological study, a characteristic feature of the fibrobronchoscopic sanitation with the human collagen type 1 was the absence of purulent inflammation of the trachea and bronchial wall.Conclusion. In the study, it was statistically proved that the early fibrobrochoscopic sanitation and application of the human collagen type 1 solution for acute lesions of the mucous membrane of the trachea and bronchi twice accelerates epithelialization of mucosal lesions without the development of purulent inflammation.